Coal mine underground fireproof flame-retardant grouting material and preparation method thereof

By using konjac glucomannan and other raw materials to form interpenetrating network gel structure and bridging effect, combined with foam stabilizer and glass scales, the problem of fire-retardant materials failing after high temperatures in the prior art is solved, and better Thermal stability and flame retardant properties ensure the long-term fireproofing effect of fire-proof materials in coal mines.

CN119286541APending Publication Date: 2025-01-10INNER MONGOLIA HUANGTAOLEGAI COAL CO LTD SHI LIN CHEM BRANCH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411359399.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing underground fire-proof and flame-retardant materials in coal mines lose their fire-proof and flame-retardant effects after baking at high temperatures, and their high-temperature shrinkage resistance is insufficient, resulting in a decrease in fire-proof effect.

Method used

The raw materials such as konjac glucomannan, ethyl orthosilicate, aluminum chloride, carbon nanofiber aerogel, nanoborocarbide and phytic acid modified shell powder are used to enhance the interpenetrating network gel structure and bridging effect. The thermal stability and flame retardant properties of the gel, combined with foam stabilizers and glass flakes, improve the mechanical strength and thermal insulation of the material.

Benefits of technology

It significantly improves the thermal stability and flame retardant properties of the material, reduces the shrinkage after high temperature, ensures the durability and durability of the fire resistance effect, and enhances the adhesion and flame retardant effect with coal rock.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005064534740000081
    Figure BDA0005064534740000081
Patent Text Reader

Abstract

The invention relates to the field of fire extinguishing materials for coal mines, and particularly discloses a coal mine underground fireproof flame-retardant grouting material and a preparation method thereof. The underground coal mine fireproof flame-retardant grouting material is prepared from the following raw materials in parts by weight: 10 to 20 parts of konjac glucomannan, 20 to 40 parts of tetraethoxysilane, 5 to 10 parts of aluminum chloride, 4 to 8 parts of carbon nanofiber aerogel, 3 to 6 parts of nano boron carbide, 3 to 6 parts of phytic acid modified shell powder, 1 to 6 parts of foaming agent, 0.5 to 4 parts of foam stabilizer and 100 to 200 parts of water. The underground coal mine fireproof and flame-retardant grouting material has the advantages of high adhesive force with the surface of coal rock, difficulty in heat shrinkage and good fireproof and flame-retardant effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of fire extinguishing materials for coal mines, and more specifically, to a fireproof and flame-retardant grouting material for underground coal mines and a preparation method thereof. Background Art

[0002] Spontaneous combustion of coal in coal mines is one of the five major disasters in coal mines. Spontaneous combustion of coal is mainly caused by the comprehensive mining and top coal caving mining and gas extraction technologies used in mining, which lead to air leakage in the goaf or a large amount of residual coal left over, which can easily lead to spontaneous combustion of coal seams.

[0003] At present, the main means of preventing coal spontaneous combustion in coal mines is to use fire-proof materials. The main fire-proof mechanism is: using quantitative addition equipment, the material is added to the water in a certain proportion to thicken the water (or mud), and then it is injected into the loose coal body with a pump (or grouting system). Under the action of pump pressure and weight, the thickened liquid penetrates into the cracks and tiny pores of the coal body and absorbs heat, which reduces the temperature of the coal body, blocks the pores and cracks of the loose coal body, and prevents oxygen molecules from penetrating into the interior of the coal body, reducing the probability of coal-oxygen contact, reducing the oxidation exothermic performance of the coal body itself, and reducing the spontaneous combustion; or it is covered on the surface of the already burned coal seam to achieve the effects of isolating oxygen, cooling, absorbing heat, and flame retardant. Fireproof materials mainly include cement, fly ash gel materials and polymer gel materials. Among them, cement and fly ash gel materials have been used relatively early and are inexpensive, non-toxic and have good permeability. They have been used to this day. Their disadvantages are large usage, long gel time, inability to be piled up high, poor fluidity, and easy to clog pipes. In addition, the gel layer is prone to cracking after formation. Therefore, polymer gel is gradually produced, which has good fluidity and short gel time.

[0004] In the prior art, a Chinese invention patent with application number CN2012100966770 discloses a polymer composite gelling agent for grouting, wherein the weight percentages are as follows: 10-25% bentonite, 5-20% cellulose, 5-20% plant gum, 10-15% calcium hydroxide, 10-25% inorganic moisture absorbent, 0.5-1.5% inorganic dispersant, 0.5-2% inorganic flocculant, 6-18% organic flocculant, 5-15% alkali metal carbonate. The above polymer gelling material has strong water solubility, good fluidity, fast gelling speed and good fire extinguishing effect, but coal spontaneously combusts. When the gel is subjected to high temperature baking, the gel will gradually lose water, shrink to a certain extent, and gradually lose the fire retardant effect. Therefore, the fire retardant effect of the gelling agent in the later stage of high temperature baking needs to be improved. Summary of the invention

[0005] In order to improve the high temperature shrinkage resistance of polymer gel flame retardant materials, the present application provides a fire retardant grouting material for underground coal mines and a preparation method thereof.

[0006] In the first aspect, the present application provides a fire-retardant grouting material for underground coal mines, adopting the following technical scheme: a fire-retardant grouting material for underground coal mines, comprising the following raw materials in parts by weight: 10-20 parts of konjac glucomannan, 20-40 parts of tetraethyl orthosilicate, 5-10 parts of aluminum chloride, 4-8 parts of carbon nanofiber aerogel, 3-6 parts of nano boron carbide, 3-6 parts of phytic acid modified shell powder, 1-6 parts of foaming agent, 0.5-4 parts of foam stabilizer, and 100-200 parts of water.

[0007] By adopting the above technical scheme, konjac glucomannan, tetraethyl orthosilicate and aluminum chloride are used as the main base materials to produce grouting materials with good thermal stability, flame retardant properties and excellent thermal insulation effects. Konjac glucomannan is a natural renewable polymer and a classic polysaccharide derivative. It is mainly composed of glucose and mannose units linked by β-1,4-glycosidic bonds, contains a small amount of acetyl groups, and has abundant sugar units on hydroxyl and carbonyl groups. Therefore, its molecular chain can easily form a gel structure with high porosity, adjustable pores and pores through hydrogen bond interactions. Tetraethyl orthosilicate is hydrolyzed to form silicon dioxide. Konjac glucomannan and tetraethyl orthosilicate form an interpenetrating network gel of konjac glucomannan and silicon dioxide, which improves the interaction force between gel molecules and enhances the structural stability of the gel network. Nanofiber aerogel is randomly attached in the network gel, and has good resilience, compressibility and thermal stability. When the network gel is subjected to high temperature, it can support a three-dimensional mesh gel structure and is not easy to shrink. Aluminum and tetraethyl orthosilicate form alumina, aluminum hydroxide and silica, which can randomly adhere to the three-dimensional network gel structure of the interpenetrating network, thereby improving thermal stability, flame retardant properties and thermal insulation effects; and carbon nanofiber aerogel has excellent flexibility, ductility, shear resistance and peeling resistance, which can improve the thermal shrinkage force of the three-dimensional network gel, improve tensile strength, increase toughness, present a good bridging effect, improve interface adhesion and weaken the crack initiation and expansion ability at the blending interface, showing enhanced tensile ductility, and can flexibly adjust with slight changes in the surface of coal rock, maintain close contact with the grouting fire-retardant grouting material and coal rock, ensure the durability of adhesion, even if there is a certain shrinkage due to heat, it will not detach, improve coverage and durability, and by increasing the interaction force between the fire-retardant grouting material and the coal rock interface, increase the wetting and penetration ability of the grouting material on the coal rock, when subjected to external force, can firmly adhere to the coal rock, reducing the risk of falling off and failure.

[0008] Nano boron carbide is used as a nano filler to act as an anchor, and its affinity for oxygen is greater than that of carbon. Therefore, boron carbide is oxidized before coal, causing the oxygen inside the coal seam to be decomposed and the content to be reduced. In addition, boron carbide produces liquid B after oxidation. 2 O 3, forming a liquid film inside the coal seam, filling the coal rock cracks, hindering the penetration of oxygen in the coal seam, improving the flame retardant effect, and increasing the mechanical properties of the gel, enhancing the density and strength of the gel, and reducing the thermal shrinkage of the gel; phytic acid modified shell powder is a rigid particle, which can provide more abundant fulcrums for the gel like nano boron carbide, making the fire retardant grouting material more bonded to the coal rock surface, and causing less damage to the toughness of the gel. Phytic acid modified shell powder has good dispersibility with konjac glucomannan and is embedded deeper in the gel network, making it more obvious to improve the strength of the gel network, and nano boron carbide can effectively prevent the formation of flame retardant grouting materials. Nano boron carbide and phytic acid modified shell powder are used as anchoring agents, which can penetrate into the microscopic cracks of coal rock, anchor in the cracks of coal rock, form a strong bonding force, and significantly increase adhesion; the addition of phytic acid modified shell powder can avoid the problem of decreased toughness caused by excessive addition of nano boron carbide and easy breakage when forming a gel. When the grouting material is injected into the cracks of coal rock, it has strong adhesion to the surface of the coal rock and can invade the tiny cracks of the coal to form a gel film that is antioxidant, has good flame retardant effect, has high adhesion, and is not easy to lose water and shrink at high temperature, which fully wraps the coal particles, isolates oxygen, and improves the fire prevention effect.

[0009] Optionally, the carbon nanofiber aerogel is prepared as follows: A polyacrylonitrile solution with a concentration of 8-10wt% is electrospun to obtain carbon nanofibers, which are oxidized at 280-300°C for 0.5-1h, heated to 800-850°C in a nitrogen atmosphere, kept warm for 20-30min, cooled to room temperature to obtain a matrix aerogel, and then crushed and dispersed in a mixture of anhydrous ethanol and deionized water, and stirred evenly to obtain a matrix solution; Add 2.5-3wt% yttrium chloride solution to the matrix solution, adjust the pH value to 7-8, stir evenly and heat to 180-200°C, react for 35-40h, filter, wash and vacuum dry. The amount of yttrium chloride added is 1.0-1.5wt% of the matrix aerogel.

[0010] By adopting the above technical scheme, the carbon nanofiber has an extremely high aspect ratio, stiffness and strength, has an excellent toughening effect, and can produce a bridging effect, thereby improving the interfacial adhesion. The carbon nanofiber is obtained by electrostatic spinning of polyacrylonitrile. First, the linear molecular chain of polyacrylonitrile is pre-oxidized, cyclized and dehydrogenated to form a heat-resistant trapezoidal structure, and then carbonized under an inert atmosphere to gradually remove non-carbon elements, and further denitrogenated and cross-linked to form a carbon-based surface and a chaotic layer graphite structure. After being made into an aerogel, it has excellent compressible resilience, can increase the thermal shrinkage performance of the gel in the gel, and is not easy to separate from the coal rock surface due to thermal shrinkage; then, yttrium hydroxide is coated on the matrix aerogel by a hydrothermal method, so that the matrix aerogel is evenly coated with yttrium hydroxide nanowhiskers , thereby improving the dispersion of carbon nanofiber aerogel in fire-retardant grouting materials and its adhesion to the surface of coal and rock. The coating of yttrium hydroxide increases the rigidity of carbon nanofiber aerogel, restricting the movement of the surrounding gel network at higher temperatures. Moreover, the three-dimensional gel network formed by carbon nanofiber aerogel and grouting materials can form an interpenetrating network structure, increasing the interface interaction between the three-dimensional gel network and carbon nanofiber aerogel, so that stress can be effectively transferred from carbon nanofiber to gel network, so that heat resistance is enhanced, and the bridging effect of carbon nanofiber aerogel can be further improved. When yttrium hydroxide decomposes at high temperature, the moisture released can dilute the combustible gas and reduce the temperature of the material, thereby effectively preventing the spread of flames. At the same time, the oxide layer formed after the decomposition of yttrium hydroxide can also serve as a physical barrier to further isolate oxygen from the material and enhance the flame retardant effect.

[0011] Optionally, the nano boron carbide is pretreated as follows: The nano boron carbide is mixed with anhydrous ether and terminal hydroxyl polybutadiene, stirred evenly, centrifuged, washed and dried, and the mass ratio of the nano boron carbide, terminal hydroxyl polybutadiene and anhydrous ether is 1:0.015-0.02:0.3-0.4.

[0012] By adopting the above technical solution, end-hydroxyl polybutadiene is used as an adhesive component and is coated on the surface of nano boron carbide as a shell layer, which can improve the dispersibility of nano silicon carbide in fire-retardant grouting materials. In addition, it has high elasticity and can improve the thermal shrinkage rate of fire-retardant grouting materials.

[0013] Optionally, the foam stabilizer is prepared by the following method: Barite, waste glass powder, calcium carbonate and boric acid are mixed, polyvinyl alcohol solution is added, ball milling is performed to obtain a mixture, and granulation is performed to obtain a foam stabilizer with a particle size of 0.1-0.2 mm.

[0014] By adopting the above technical scheme, barite has high heat resistance and mechanical strength, can increase the density and heat resistance stability of gel, and waste glass powder is domestic waste, which is mixed with barite as a spherical foam stabilizer, and the outer wall of the bubble is evenly adhered to the surface of the foam stabilizer, not easy to merge, diffuse and collapse, the liquid film is relatively evenly distributed, not easy to break, which greatly delays the speed of foam collapse, increases the stability of the foam, and greatly improves the fire extinguishing efficiency; the foam stabilizer is injected into the coal seam along with the grouting material, and when the coal seam spontaneously combusts, when the temperature is high, the waste glass powder can use calcium carbonate as a foaming agent and boric acid as a co-solvent to produce a glass foaming effect, forming countless tiny bubbles, thereby forming a unique insulation layer when the coal rock spontaneously combusts, effectively preventing the transfer of flame and heat, thereby playing a flame retardant effect, and the foamed glass has good stability, can maintain the structural integrity of the gel at high temperature, and improve the flame retardant effect of the coal rock in the later stage of spontaneous combustion.

[0015] Optionally, the weight proportions of raw materials in the foam stabilizer are as follows: 1-2 parts of barite, 1-2 parts of waste glass powder, 0.03-0.06 parts of calcium carbonate and 0.01-0.02 parts of boric acid, and 0.08-0.16 parts of polyvinyl alcohol solution.

[0016] By adopting the above technical solution, the above amounts of raw materials can produce a foam stabilizer with excellent flame retardancy, foam stability and thermal stability.

[0017] Optionally, the preparation method of the phytic acid modified shell powder is: The shell powder is mixed with water and subjected to ultrasonic treatment to prepare a suspension having a concentration of 9-10 wt %; Phytic acid is added dropwise to the suspension until no bubbles are generated, the suspension is collected by filtration, and the suspension is centrifuged. The centrifuged precipitate is freeze-dried to obtain phytic acid-modified shell powder.

[0018] By adopting the above technical solution, phytic acid is a natural green bio-based material rich in phosphorus, with a highly symmetrical molecular structure. There are 6 negatively charged phosphate groups connected to the benzene ring, and the phosphate group is further connected to 12 hydroxyl groups that can be hydrolyzed into hydrogen ions. The unique structure allows phytic acid to react with metal cations to form a water-insoluble complex. Due to the presence of a large amount of phosphorus in phytic acid, the resulting complex also has excellent flame retardant ability; during the thermal degradation process, the complex will generate a strong dehydrating agent to promote the formation of a carbonized layer, blocking oxygen and heat transfer, and at the same time generate a non-volatile glassy phosphide covering the surface of the coal rock, thereby hindering the flame from spreading into the interior of the coal rock and effectively protecting the coal seam.

[0019] Optionally, the foaming agent includes hydrogen peroxide and sodium fatty alcohol polyoxyethylene ether sulfate in a mass ratio of 1:0.1-0.3.

[0020] By adopting the above technical solution, the foaming agent can produce a large amount of foam to cover the surface of the coal, which plays a role in heat insulation and oxygen isolation in the early stage.

[0021] Optionally, 3-6 parts by weight of glass flakes are also added to the fire-retardant grouting material.

[0022] By adopting the above technical scheme, the glass flakes enter the coal seam along with the grouting material, and form a protective layer with layers of staggered overlap in the coal seam. Therefore, the glass flakes have good anti-penetration ability and can prevent the penetration of oxygen; the lamellar structure of the glass flakes divides the gel network into many layered structures, making the penetration path of oxygen and heat tortuous, thereby delaying the transmission time of the combustion medium, thereby improving the fire prevention effect; and the coal seam produces spontaneous combustion, and the gel network will produce a shrinkage force when heated. The glass flakes can move along with the shrinkage stress during the thermal contraction, so that the shrinkage stress does work on the glass flakes, reducing the existence of residual stress, and then reducing the existence of cracks and interface voids, so that the gel network maintains good shape stability, and has a strong bonding with the coal rock surface, and has better fire prevention performance.

[0023] In a second aspect, the present application provides a method for preparing a fire-retardant grouting material for underground coal mines, using the following technical solution: A method for preparing a fire-proof and flame-retardant grouting material for an underground coal mine comprises the following steps: S1, add konjac glucomannan to water twice its mass, raise the temperature to 70-75°C and stir to swell; S2. Evenly mix ethyl orthosilicate, ethanol and the remaining water, adjust the pH value to 2-3, add aluminum chloride, stir at 40-45° C. for 4-5 h, then adjust the pH value to 8-9, stir at 55-60° C. for 0.5-1 h to obtain a blend; S3. Mix the blend with the product obtained in step S1, stir evenly, add carbon nanofiber aerogel, foaming agent, foam stabilizer, boron carbide and phytic acid modified shell powder, glass flakes, mix well, and prepare a fire-retardant grouting material.

[0024] By adopting the above technical scheme, tetraethyl orthosilicate, konjac glucomannan, aluminum chloride and carbon nanofiber aerogel can form an interpenetrating network gel. Under the bridging effect of carbon nanofiber aerogel, the adhesion between the gel and the coal rock surface can be increased, and the thermal stability of the gel can be improved. Nano-boron carbide and phytic acid-modified shell powder can increase the density and rigidity of the gel and reduce thermal shrinkage.

[0025] Optionally, when the pH is adjusted to 2-3, boric acid with a concentration of 0.5-1 mol / L is used, and when the pH is adjusted to 8-9, a sodium hydroxide solution with a concentration of 1-1.5 mol / L is used.

[0026] By adopting the above technical solution and using boric acid to condition the pH, the dehydration reaction of the boric acid group produces a large amount of water, which causes a large amount of combustion heat loss, and can further suppress combustion. In addition, a higher residual carbon rate can also isolate smoke release and heat transfer.

[0027] In summary, this application has the following beneficial effects: 1. Since the present application adopts konjac glucomannan, aluminum chloride and tetraethyl orthosilicate, an interpenetrating network gel can be formed and injected into the cracks of coal rocks to block heat and oxygen and achieve a good flame retardant effect. Moreover, by adding carbon nanofiber aerogel, nano boron carbide and phytic acid modified shell powder, the density and mechanical strength of the gel can be improved, and the heat resistance and thermal stability can be improved. It is not easy to produce thermal shrinkage in the later stage of high temperature and detach from the coal rock surface, thereby losing the flame retardant effect.

[0028] 2. In the present application, it is preferred to coat yttrium hydroxide when preparing carbon nanofiber aerogel, so as to load hydroxide rare earth whiskers on the carbon nanofiber aerogel, thereby further improving the bridging effect of the carbon nanofiber aerogel, improving the wettability and adhesion of the grouting material, and increasing the thermal stability and flame retardant effect.

[0029] 3. In the present application, glass flakes are preferably added to the grouting material, which are superimposed on each other in the coal-rock gaps to form a protective layer, thereby reducing the penetration of oxygen and heat, improving the flame retardant effect, and increasing the thermal shrinkage of the gel to improve its thermal stability. DETAILED DESCRIPTION

[0030] The following examples further illustrate the present application in detail.

[0031] Preparation Example 1-3 of Carbon Nanofiber Aerogel Preparation Example 1: (1) Add 80 g of polyacrylonitrile to N,N-dimethylformamide, heat to 60° C. and stir in a water bath for 2 h to obtain a polyacrylonitrile solution with a concentration of 10 wt %, wherein the molecular weight of the polyacrylonitrile is 90,000; (2) A 10 wt% polyacrylonitrile solution was electrospun to obtain carbon nanofibers, which were oxidized at 280°C for 1 h, heated to 800°C at a rate of 5°C / min in a nitrogen atmosphere, kept warm for 30 min, and cooled to room temperature to obtain a matrix aerogel. The aerogel was crushed to obtain a carbon nanofiber aerogel with a length of 15 μm. The spinning voltage was 15 kV, the spinning speed was 15 mL / h, and the receiving distance was 15 cm.

[0032] Preparation Example 2: (1) 80 g of polyacrylonitrile was added to N,N-dimethylformamide, and the mixture was heated to 60° C. and stirred in a water bath for 2 h to obtain a polyacrylonitrile solution having a concentration of 10 wt %, wherein the molecular weight of the polyacrylonitrile was 90,000; (2) A 10 wt% polyacrylonitrile solution was electrospun to obtain carbon nanofibers, which were oxidized at 280°C for 1 h, heated to 800°C at a rate of 5°C / min in a nitrogen atmosphere, kept warm for 30 min, and cooled to room temperature to obtain a matrix aerogel. The spinning voltage was 15 kV, the spinning speed was 15 mL / h, and the receiving distance was 15 cm. (3) 100 g of the matrix aerogel was crushed and dispersed into a 200 g mixture of anhydrous ethanol and deionized water in a volume ratio of 1:3, and stirred evenly to prepare a matrix solution; (4) A 3 wt % yttrium chloride aqueous solution was added to the matrix solution, and the pH value was adjusted to 8 with a 5 % sodium hydroxide aqueous solution. After stirring for 4 h, the temperature was raised to 180 ° C, and the reaction was continued for 40 h. The solution was cooled to room temperature, filtered, washed, and vacuum dried for 8 h at a vacuum degree of 0.08 MPa and a temperature of 80 ° C. The amount of yttrium chloride added was 1.5 wt % of the matrix aerogel.

[0033] Preparation Example 3: (1) Add 80 g of polyacrylonitrile to N,N-dimethylformamide, heat to 60° C. and stir in a water bath for 2 h to obtain a polyacrylonitrile solution with a concentration of 8 wt %. The molecular weight of the polyacrylonitrile is 90,000. (2) A polyacrylonitrile solution with a concentration of 8 wt% was electrospun to obtain carbon nanofibers, which were oxidized at 300 °C for 0.5 h, heated to 850 °C at a rate of 5 °C / min in a nitrogen atmosphere, kept warm for 20 min, and cooled to room temperature to obtain a matrix aerogel. The spinning voltage was 15 kV, the spinning speed was 15 mL / h, and the receiving distance was 15 cm. (3) 100 g of the matrix aerogel was crushed and dispersed into a 200 g mixture of anhydrous ethanol and deionized water in a volume ratio of 1:3, and stirred evenly to prepare a matrix solution; (4) A 2.5 wt% yttrium chloride aqueous solution was added to the matrix solution, and the pH value was adjusted to 9 with a 5% sodium hydroxide aqueous solution. After stirring for 4 h, the temperature was raised to 200°C, and the reaction was carried out for 35 h. The solution was cooled to room temperature, filtered, washed, and vacuum dried for 8 h at a vacuum degree of 0.08 MPa and a temperature of 80°C. The amount of yttrium chloride added was 1.0 wt% of the matrix aerogel.

[0034] Preparation Example 4-5 of Phytic Acid Modified Shell Powder Preparation Example 4: 50 g of shell powder was mixed with distilled water, stirred for 1 hour, and then ultrasonically vibrated for 30 minutes to prepare a suspension with a concentration of 10 wt%; Phytic acid was added dropwise to the suspension until no bubbles were generated. After standing for 2 hours, the suspension was filtered and collected. The suspension was centrifuged to collect the centrifugal precipitate. The centrifugal precipitate was freeze-dried at -40°C for 24 hours to obtain phytic acid-modified shell powder.

[0035] Preparation Example 5: 50 g of shell powder was mixed with distilled water, stirred for 1 hour, and then ultrasonically vibrated for 30 minutes to prepare a suspension with a concentration of 9 wt%; Phytic acid was added dropwise to the suspension until no bubbles were generated. After standing for 2 hours, the suspension was filtered and collected. The suspension was centrifuged to collect the centrifugal precipitate. The centrifugal precipitate was freeze-dried at -40°C for 24 hours to obtain phytic acid-modified shell powder.

[0036] Preparation Example 6-9 of Foam Stabilizer Preparation Example 6: 20 g of barite, 20 g of waste glass powder, 0.06 g of calcium carbonate and 0.02 g of boric acid were mixed, 0.16 g of a 3 wt % polyvinyl alcohol aqueous solution was added, the mixture was ball-milled, and granulated to obtain a foam stabilizer with a particle size of 0.2 mm.

[0037] Preparation Example 7: 10 g of barite, 10 g of waste glass powder, 0.03 g of calcium carbonate and 0.01 g of boric acid were mixed, 0.08 g of a 3 wt % polyvinyl alcohol aqueous solution was added, the mixture was ball-milled, and granulated to obtain a foam stabilizer with a particle size of 0.1 mm.

[0038] Preparation Example 8: 20 g of waste glass powder, 0.06 g of calcium carbonate and 0.02 g of boric acid were mixed, 0.16 g of a 3 wt% polyvinyl alcohol aqueous solution was added, the mixture was ball-milled, and granulated to obtain a foam stabilizer with a particle size of 0.2 mm.

[0039] Preparation Example 9: 20 g of barite and 20 g of waste glass powder were mixed, 0.16 g of a 3 wt % polyvinyl alcohol aqueous solution was added, and the mixture was ball-milled to obtain a mixture, and granulated to obtain a foam stabilizer with a particle size of 0.2 mm. Example

[0040] Example 1: A fire-retardant grouting material for underground coal mines, the raw material dosage of which is shown in Table 1, wherein konjac glucomannan is selected from Nanjing Bermuda Biotechnology Co., Ltd., model 37220-17-0, carbon nanofiber aerogel is made by Preparation Example 1, nano boron carbide has a particle size of 50nm, selected from Beijing Mairida Technology, item number B802552, phytic acid modified shell powder is made by Preparation Example 4, the foaming agent includes hydrogen peroxide and sodium fatty alcohol polyoxyethylene ether sulfate in a mass ratio of 1:0.3, the sodium fatty alcohol polyoxyethylene ether sulfate is selected from Guangzhou Maoting Chemical Co., Ltd., model AES, and the foam stabilizer is glass microspheres with a particle size of 0.2mm.

[0041] The method for preparing the above-mentioned fire-proof and flame-retardant grouting material for underground coal mines comprises the following steps: S1, add konjac glucomannan to water twice its mass, heat to 70°C and stir to swell; S2, ethyl orthosilicate was mixed with ethanol and the remaining water, the pH value was adjusted to 2 with 1 mol / L boric acid, aluminum chloride was added, and the mixture was stirred at 40°C for 5 h, and then the pH value was adjusted to 8 with 1 mol / L sodium hydroxide solution, and the mixture was stirred at 60°C for 0.5 h to obtain a blend, wherein the mass ratio of water to ethanol was 4:1; S3, mixing the blend with the product obtained in step S1, adding carbon nanofiber aerogel, foaming agent, foam stabilizer, boron carbide and phytic acid modified shell powder after stirring evenly, mixing evenly, and obtaining a fire-retardant grouting material.

[0042] Table 1 Raw material dosage of fire retardant grouting materials in Examples 1-4 Example 2: A fire-retardant grouting material for underground coal mines, the raw material dosage of which is shown in Table 1, wherein konjac glucomannan is selected from Nanjing Bermuda Biotechnology Co., Ltd., model 37220-17-0, carbon nanofiber aerogel is made by Preparation Example 1, nano boron carbide has a particle size of 50nm, selected from Beijing Mairida Technology, item number B802552, phytic acid modified shell powder is made from Preparation Example 5, the foaming agent includes hydrogen peroxide and sodium fatty alcohol polyoxyethylene ether sulfate in a mass ratio of 1:0.1, sodium fatty alcohol polyoxyethylene ether sulfate is selected from Guangzhou Maoting Chemical Co., Ltd., model AES, and the foam stabilizer is glass microspheres with a particle size of 0.1mm.

[0043] The method for preparing the above-mentioned fire-proof and flame-retardant grouting material for underground coal mines comprises the following steps: S1, add konjac glucomannan to water twice its mass, heat to 75°C and stir to swell; S2, ethyl orthosilicate, ethanol and the remaining water were mixed evenly, the pH value was adjusted to 3 with 0.5 mol / L boric acid, aluminum chloride was added, and the mixture was stirred at 45°C for 4 hours, and then the pH value was adjusted to 9 with 1.5 mol / L sodium hydroxide solution, and the mixture was stirred at 55°C for 1 hour to obtain a blend, wherein the mass ratio of water to ethanol was 4:1; S3, S3, mix the blend with the product obtained in step S1, stir evenly, add carbon nanofiber aerogel, foaming agent, foam stabilizer, boron carbide and phytic acid modified shell powder, mix evenly, and prepare a fire-retardant grouting material.

[0044] Example 3-4: A fire-retardant grouting material for underground coal mines, which differs from Example 1 in that the amounts of raw materials used are as shown in Table 1.

[0045] Example 5: A fire-retardant grouting material for underground coal mines. The difference from Example 1 is that the carbon nanofiber aerogel is made from Preparation Example 2.

[0046] Example 6: A fire-retardant grouting material for underground coal mines, which differs from Example 1 in that the carbon nanofiber aerogel is made from Preparation Example 3.

[0047] Example 7: A fire-retardant grouting material for underground coal mines. The difference from Example 5 is that the boron carbide is pretreated as follows: nano-boron carbide is mixed with anhydrous ether and terminal hydroxyl polybutadiene, stirred evenly, centrifuged, washed, and dried at 70°C for 10 hours. The mass ratio of nano-boron carbide, terminal hydroxyl polybutadiene and anhydrous ether is 1:0.015:0.3.

[0048] Example 8: A fire-retardant grouting material for underground coal mines, which is different from Example 5 in that the boron carbide is pretreated as follows: The nano boron carbide is mixed with anhydrous ether and terminal hydroxyl polybutadiene, stirred evenly, centrifuged, washed and dried, and the mass ratio of the nano boron carbide, terminal hydroxyl polybutadiene and anhydrous ether is 1:0.02:0.4.

[0049] Example 9: A fire-retardant grouting material for underground coal mines, which differs from Example 1 in that the foam stabilizer is barite.

[0050] Example 10: A fire-retardant grouting material for underground coal mines, which differs from Example 1 in that the foam stabilizer is made from Preparation Example 6.

[0051] Example 11: A fire-retardant grouting material for underground coal mines, which differs from Example 1 in that the foam stabilizer is made from Preparation Example 7.

[0052] Example 12: A fire-retardant grouting material for underground coal mines, which differs from Example 1 in that the foam stabilizer is made from Preparation Example 8.

[0053] Example 13: A fire-retardant grouting material for underground coal mines, which differs from Example 1 in that the foam stabilizer is made from Preparation Example 9.

[0054] Example 14: A fire-retardant grouting material for underground coal mines. The difference from Example 11 is that the raw materials of the fire-retardant grouting material also contain 6 kg of glass flakes with a particle size of 200 mesh. The difference in the preparation method is that in step S3, the blend is mixed with the result of step S1, and after stirring evenly, carbon nanofiber aerogel, foaming agent, foam stabilizer, boron carbide and phytic acid modified shell powder, and glass flakes are added and mixed evenly to obtain the fire-retardant grouting material.

[0055] Example 15: A fire-retardant grouting material for underground coal mines. The difference from Example 1 is that the raw materials of the fire-retardant grouting material also contain 3 kg of glass flakes with a particle size of 200 mesh. The difference in the preparation method is that in step S3, the blend is mixed with the result of step S1, and after stirring evenly, carbon nanofiber aerogel, foaming agent, foam stabilizer, boron carbide and phytic acid modified shell powder, and glass flakes are added and mixed evenly to obtain the fire-retardant grouting material.

[0056] Example 16: A fire-retardant grouting material for underground coal mines, which differs from Example 7 in that the foam stabilizer is made from Preparation Example 6.

[0057] Example 17: A fire-retardant grouting material for underground coal mines. The difference from Example 7 is that the foam stabilizer is made from Preparation Example 6, and 6 kg of glass flakes with a particle size of 200 mesh are also added. The difference in the preparation method is that in step S3, the blend is mixed with the result of step S1, and after stirring evenly, carbon nanofiber aerogel, foaming agent, foam stabilizer, boron carbide and phytic acid modified shell powder, glass flakes are added and mixed evenly to obtain a fire-retardant grouting material.

[0058] Comparative Example Comparative Example 1: A fire-retardant grouting material for underground coal mines, which differs from Example 1 in that an equal amount of nano-boron carbide is used to replace phytic acid-modified shell powder.

[0059] Comparative Example 2: A fire-retardant grouting material for underground coal mines, which differs from Example 1 in that nano boron carbide and phytic acid-modified shell powder are not added.

[0060] Comparative Example 3: A fire-retardant grouting material for underground coal mines, which differs from Example 1 in that an equal amount of shell powder is used to replace the phytic acid-modified shell powder.

[0061] Comparative Example 4: A fire-retardant grouting material for underground coal mines, which differs from Example 1 in that no carbon nanofiber aerogel is added.

[0062] Comparative Example 5: A fire-retardant grouting material for underground coal mines, which differs from Example 1 in that no aluminum chloride is added.

[0063] Comparative Example 6: A method for preparing a polymer composite gelling agent for grouting, comprising the following steps: (A) Composite gelling agent: According to weight percentage, 20% of bentonite, 20% of calcium sulfate, 10% of calcium hydroxide, 12% of vegetable gum, 12% of carboxymethyl cellulose, 16% of polyacrylamide, 8% of sodium bicarbonate, 0.6% of sodium hydroxide, and 1.4% of ferric chloride are weighed and mixed uniformly to prepare a gelling agent; (B) Slurry preparation (by mass): (1) Screen loess into powder with a particle size of less than 8 mm, weigh 500 parts of soil and 400 parts of water and mix them evenly into slurry; (2) Then weigh 1 part of gelling agent; (3) Add the weighed gelling agent to 100 parts of water and mix them evenly to form a gelling agent aqueous solution; (4) Inject the mixed gelling agent aqueous solution into the mud and water slurry at a certain pressure; (5) Further mix and stir the mud and water slurry injected with the gelling agent aqueous solution to form a gel after 3 minutes, and inject it into the empty area, cracks and damaged coal surface for treatment.

[0064] Performance testing The fireproof and flame-retardant grouting materials were prepared according to the methods in the examples and comparative examples, and their properties were tested according to the following methods. The test results are recorded in Table 2.

[0065] 1. Compressive strength: The RMT-150B rock mechanics experimental system was used for the experiment. The sample was placed on the base of the experimental instrument and the experimental system operation interface was opened for testing.

[0066] 2. Inhibition performance: The inhibition rate at a coal temperature of 100°C is tested in accordance with MT / T700-1997 "General Technical Requirements for Inhibitors for Coal Mine Fire Prevention".

[0067] 3. Thermal stability: Take 100g of grouting material, place it in a constant temperature drying oven and heat it uniformly to 100℃, keep it warm for 168h, and test the weight loss rate of the grouting material.

[0068] 4. Viscosity: Use DV-1 rotary intelligent digital display viscometer, the test environment is 20℃ and the relative humidity is 50%.

[0069] Table 2 Performance test results of fire retardant grouting materials project Compressive strength / MPa Inhibition performance / % Weight loss rate / % Viscosity / mPa.s Example 1 1.85 73.3 18.9 4352 Example 2 1.76 72.4 19.5 4294 Example 3 1.82 72.8 19.1 4315 Example 4 1.78 73.1 19.4 4308 Example 5 1.98 74.5 17.6 4402 Example 6 1.95 74.3 17.4 4389 Example 7 2.11 74.8 16.3 4396 Example 8 2.13 74.9 16.1 4403 Example 9 1.84 73.2 18.8 4345 Example 10 1.93 74.3 17.8 4327 Embodiment 11 1.94 74.5 17.9 4332 Example 12 1.87 73.8 18.5 4345 Embodiment 13 1.86 73.6 18.5 4348 Embodiment 14 2.05 74.6 16.8 4341 Embodiment 15 2.03 74.3 16.9 4335 Example 16 2.21 75.6 15.7 4394 Embodiment 17 2.45 76.5 14.8 4405 Comparative Example 1 1.89 71.4 20.4 4290 Comparative Example 2 1.75 70.5 21.5 4272 Comparative Example 3 1.82 72.3 19.8 4337 Comparative Example 4 1.69 71.1 19.5 4319 Comparative Example 5 1.72 70.2 20.8 4345 Comparative Example 6 0.58 73.2 25.4 4236 It can be seen from the data in Table 2 that the fire-retardant grouting materials made from raw materials such as carbon nanofiber aerogel, nano boron carbide and phytic acid modified shell powder used in Examples 1-4 have good permeability to coal rock cracks and strong stability. They can be injected into areas that need to be plugged, cover the coal body or seal the cracks, isolate oxygen and control air leakage, thereby preventing spontaneous combustion of coal rocks.

[0070] Compared with Example 1, Examples 5 and 6 respectively use the carbon nanofiber aerogel prepared in Preparation Example 2 and Preparation Example 3, and coat yttrium hydroxide on the base aerogel. Table 2 shows that the fire-retardant grouting materials prepared in Examples 5 and 6 have better retardant effect, stronger rigidity, better heat resistance, and improved dispersibility of the carbon nanofiber aerogel, thereby increasing the bridging effect and increasing adhesion.

[0071] Compared with Example 6, Example 7 and Example 8 also use terminal hydroxyl polybutadiene to pretreat the nano boron carbide. By comparison, it can be seen that the fire-retardant grouting materials prepared in Example 7 and Example 8 have better tensile strength and retardant properties, and have a small weight loss rate at high temperature and better thermal stability.

[0072] Compared with Example 1, Example 9 uses barite as a foam stabilizer. Table 2 shows that the retardant performance, compressive strength and thermal stability of the fire-retardant grouting material are not much different from those of Example 1.

[0073] In Example 10 and Example 11, the foam stabilizers prepared in Preparation Example 6 and Preparation Example 7 were used respectively. Compared with Example 1, the compressive strength of the fire-retardant grouting material was slightly increased, the retardancy rate was increased, the fireproof effect was enhanced, the weight loss rate was reduced, and the thermal stability was enhanced.

[0074] Example 12 uses the foam stabilizer prepared in Preparation Example 8, and no barite is added in Preparation Example 8. It can be seen that the compressive strength of the fire-retardant grouting material prepared in Example 12 decreases, the weight loss rate increases, and the fireproof effect weakens.

[0075] In Example 13, the foam stabilizer prepared in Preparation Example 9 was used. In Preparation Example 9, no calcium carbonate and boric acid were added. Only barite and waste glass powder were mixed and granulated with polyvinyl alcohol. The foam stabilizer prepared in this way had improved catalytic performance compared with Example 1, but decreased catalytic performance, compressive strength, etc. compared with Examples 10 and 11.

[0076] Compared with Example 1, a certain amount of glass flakes are added in Example 14 and Example 15. As shown in Table 2, the compressive strength, retardant performance and thermal stability of the fire-retardant grouting material are enhanced.

[0077] Compared with Example 7, Example 16 also uses the foam stabilizer prepared in Preparation Example 6. Table 2 shows that compared with Example 1 and Example 7, the fire-retardant grouting material prepared in Example 16 has enhanced compressive strength, increased retardant effect, and better thermal stability.

[0078] Compared with Example 7, Example 17 not only uses the foam stabilizer prepared in Preparation Example 6, but also adds glass flakes. The fire-retardant grouting material prepared in Example 17 has the best performance.

[0079] In Comparative Example 1, nano boron carbide is used to replace phytic acid modified shell powder, and in Comparative Example 2, nano boron carbide and phytic acid modified shell powder are not added. Compared with Example 1, the compressive strength of the fire-retardant grouting materials prepared in Comparative Example 1 and Comparative Example 2 decreases, the flame retardant effect weakens, and the thermal stability deteriorates. The coal rock is prone to shrinkage after spontaneous combustion and loses the fire-retardant effect.

[0080] In Comparative Example 3, shell powder was used instead of phytic acid modified shell powder. Table 2 shows that the thermal stability of the fire-retardant grouting material decreased and the thermal shrinkage rate increased.

[0081] No carbon nanofiber aerogel was added in Comparative Example 4, and no aluminum chloride was added in Comparative Example 5. Compared with Example 1, the weight loss rate of the fire-retardant grouting materials prepared in Comparative Examples 4 and 5 increased at high temperatures and their stability decreased.

[0082] Comparative Example 6 is a grouting gel prepared by the prior art. It can be seen that its compressive strength is low, and its weight loss rate is large at high temperature, its thermal shrinkage is large, and its fire extinguishing effect decreases in the later stage of high-temperature baking.

[0083] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A fire-retardant grouting material for underground coal mines, characterized in that: The invention comprises the following raw materials in parts by weight: 10-20 parts of konjac glucomannan, 20-40 parts of tetraethyl orthosilicate, 5-10 parts of aluminum chloride, 4-8 parts of carbon nanofiber aerogel, 3-6 parts of nano boron carbide, 3-6 parts of phytic acid modified shell powder, 1-6 parts of foaming agent, 0.5-4 parts of foam stabilizer and 100-200 parts of water.

2. The fire-retardant grouting material for underground coal mines according to claim 1, characterized in that: The preparation method of the carbon nanofiber aerogel is as follows: A polyacrylonitrile solution with a concentration of 8-10wt% is electrospun to obtain carbon nanofibers, which are oxidized at 280-300°C for 0.5-1h, heated to 800-850°C under a nitrogen atmosphere, kept warm for 20-30min, and cooled to room temperature to obtain a matrix aerogel, which is crushed and dispersed in a mixture of anhydrous ethanol and deionized water, and stirred evenly to obtain a matrix solution; Add 2.5-3wt% yttrium chloride solution to the matrix solution, adjust the pH value to 7-8, stir evenly and heat to 180-200°C, react for 35-40h, filter, wash and vacuum dry. The amount of yttrium chloride added is 1.0-1.5wt% of the matrix aerogel.

3. The fire-retardant grouting material for underground coal mines according to claim 1, characterized in that: The nano boron carbide is pretreated as follows: The nano boron carbide is mixed with anhydrous ether and terminal hydroxyl polybutadiene, stirred evenly, centrifuged, washed and dried, and the mass ratio of the nano boron carbide, terminal hydroxyl polybutadiene and anhydrous ether is 1:0.015-0.02:0.3-0.

4.

4. The fire-retardant grouting material for underground coal mines according to claim 1, characterized in that: The foam stabilizer is prepared by the following method: Barite, waste glass powder, calcium carbonate and boric acid are mixed, polyvinyl alcohol solution is added, ball milling is performed to obtain a mixture, and granulation is performed to obtain a foam stabilizer with a particle size of 0.1-0.2 mm.

5. The fire-retardant grouting material for underground coal mines according to claim 4, characterized in that: The weight proportions of raw materials in the foam stabilizer are as follows: 1-2 parts of barite, 1-2 parts of waste glass powder, 0.03-0.06 parts of calcium carbonate, 0.01-0.02 parts of boric acid, and 0.08-0.16 parts of polyvinyl alcohol solution.

6. The fire-retardant grouting material for underground coal mines according to claim 1, characterized in that: The preparation method of the phytic acid modified shell powder: The shell powder is mixed with water and subjected to ultrasonic treatment to prepare a suspension having a concentration of 9-10 wt %; Phytic acid is added dropwise to the suspension until no bubbles are generated, the suspension is collected by filtration, and the suspension is centrifuged. The centrifuged precipitate is freeze-dried to obtain phytic acid-modified shell powder.

7. The fire-retardant grouting material for underground coal mines according to claim 1, characterized in that: The foaming agent comprises hydrogen peroxide and sodium fatty alcohol polyoxyethylene ether sulfate in a mass ratio of 1:0.1-0.

3.

8. The fire-retardant grouting material for underground coal mines according to claim 1, characterized in that: 3-6 parts by weight of glass flakes are also added to the fireproof and flame-retardant grouting material.

9. The method for preparing the fireproof and flame-retardant grouting material for underground coal mines according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, add konjac glucomannan to water twice its mass, raise the temperature to 70-75°C and stir to swell; S2. Evenly mix ethyl orthosilicate, ethanol and the remaining water, adjust the pH value to 2-3, add aluminum chloride, stir at 40-45° C. for 4-5 h, then adjust the pH value to 8-9, stir at 55-60° C. for 0.5-1 h to obtain a blend; S3. Mix the blend with the product obtained in step S1, stir evenly, add carbon nanofiber aerogel, foaming agent, foam stabilizer, boron carbide and phytic acid modified shell powder, glass flakes, mix well, and prepare a fire-retardant grouting material.

10. The method for preparing the fireproof and flame-retardant grouting material for underground coal mines according to claim 9, characterized in that: When the pH is adjusted to 2-3, boric acid with a concentration of 0.5-1 mol / L is used, and when the pH is adjusted to 8-9, a sodium hydroxide solution with a concentration of 1-1.5 mol / L is used.